2005
DOI: 10.1056/nejmoa042087
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel versus Aspirin and Esomeprazole to Prevent Recurrent Ulcer Bleeding

Abstract: Among patients with a history of aspirin-induced ulcer bleeding whose ulcers had healed before they received the study treatment, aspirin plus esomeprazole was superior to clopidogrel in the prevention of recurrent ulcer bleeding. Our finding does not support the current recommendation that patients with major gastrointestinal intolerance of aspirin be given clopidogrel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
259
1
35

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 560 publications
(315 citation statements)
references
References 24 publications
12
259
1
35
Order By: Relevance
“…The combination of esomeprazole and LDA is superior to clopidogrel in preventing ulcer complications in patients who have a past history of LDA-related peptic ulcer bleeding [133,134]. The long-term incidence of recurrent ulcer bleeding with LDA use is low after H. pylori eradication [135].…”
Section: Commentmentioning
confidence: 99%
“…The combination of esomeprazole and LDA is superior to clopidogrel in preventing ulcer complications in patients who have a past history of LDA-related peptic ulcer bleeding [133,134]. The long-term incidence of recurrent ulcer bleeding with LDA use is low after H. pylori eradication [135].…”
Section: Commentmentioning
confidence: 99%
“…However, more recent studies have reported a significantly increased risk of GI bleeding during treatment with clopidogrel. 14,15 Importantly, the risk of bleeding increases when combining clopidogrel with aspirin. 16,17 Currently, the use of proton pump inhibitors is the prevailing strategy for the prevention of GI bleeding during antiplatelet therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Esta "mejor tolerancia" gastrointestinal de clopidogrel sugiere que su empleo sería ventajoso en pacientes con riesgo de úlceras por AAS, sin embargo recientemente se ha descrito que en pacientes con historial de úlceras sangrantes causadas por AAS, el tratamiento con AAS+esomeprazol presenta una menor incidencia de recurrencia de la úlcera que el uso de clopidogrel 13 . Asimismo, un estudio de ingresos hospitalarios confirma que el riesgo de hemorragias gastrointestinales es menor en la asociación AAS+ un inhibidor de la bomba de protones que con clopidogrel 14 .…”
Section: Discussionunclassified